Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

If e1=((2^1/3)-1)^1/3 e2=(9^-1/3)-((2/9)^1/3)+((4/9)^1/3) then prove that e1=e2.

If
e1=((2^1/3)-1)^1/3
e2=(9^-1/3)-((2/9)^1/3)+((4/9)^1/3)
then prove that
e1=e2.

Grade:

1 Answers

Mostafijur Rahaman
40 Points
7 years ago
apply log.

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free